2019
DOI: 10.1128/jb.00712-18
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of cysL Inhibits Biofilm Formation by Activating the Disulfide Stress Regulator Spx in Bacillus subtilis

Abstract: Bacillus subtilis forms biofilms in response to internal and external stimuli. I previously showed that the cysL deletion mutant was defective in biofilm formation, but the reason for this remains unidentified. CysL is a transcriptional activator of the cysJI operon, which encodes sulfite reductase, an enzyme involved in cysteine biosynthesis. Decreased production of sulfite reductase led to biofilm formation defects in the ΔcysL mutant. The ΔcysL mutation was suppressed by disrupting cysH operon genes, whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Spx has been reported to inhibit biofilm formation [30], and inactivation of spx can enhance the biofilm formation in B. subtilis [31]. However, Δspx showed a colony morphology and biofilm with less wrinkles but could be partially restored by compensation of spx , indicating that spx plays a positive role in the biofilm formation here.…”
Section: Discussionmentioning
confidence: 84%
“…Spx has been reported to inhibit biofilm formation [30], and inactivation of spx can enhance the biofilm formation in B. subtilis [31]. However, Δspx showed a colony morphology and biofilm with less wrinkles but could be partially restored by compensation of spx , indicating that spx plays a positive role in the biofilm formation here.…”
Section: Discussionmentioning
confidence: 84%
“…Spx has been reported to inhibit biofilm formation [33], and inactivation of spx can enhance the biofilm formation in B. subtilis [34]. However, Δ spx showed a colony morphology and biofilm with less wrinkles but could be partially restored by compensation of spx , indicating that spx plays a positive role in the biofilm formation here.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported that increased CPS content contributes to increased biofilm formation [ 52 , 53 ]. The quantitative analysis of the biofilm’s CV staining revealed that significantly more biofilm adhered to the glass surface in MR14 compared with ATCC 17978 and MR14C ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%